Impacto del COVID-19 en las actividades económicas-financieras de las cooperativas de Ahorro y Crédito del Segmento Cuatro - Cedeño Arteaga, Gema Stefanía (2023)
The objective of this research work was to analyze the impact of COVID-19 on the economic-financial activities of the Ecuadorian Savings and Credit Cooperatives of segment four for the identification of the level of variation of the values of the accounts of the financial statements considering the years 2019 to 2022. Taking as a population sample a total of 95 savings and credit cooperatives, which provided continuous information during the years studied, a cross-sectional, causal, bibliographic, exploratory and quantitative research approach was used. In the same way, it was necessary to apply methods such as analytical and descriptive; the main techniques were literature review, financial analyses, such as horizontal and vertical analysis, and forecasting techniques. In turn, the pearl monitoring system was an essential part of the investigation. The results show that COVID-19 had its greatest negative impact in the first year of the pandemic, that is, in 2020, with regard to the credit portfolio and accounts receivable, with a decrease equivalent to 2% and 9%, respectively. By applying the PEARLS methodology, the Financial Structure (E) indicators for the pandemic years (2019-2022) yielded positive results in terms of the share of the net portfolio, which remained in a range between 70% and 73 %. Net investments also remained positive, as percentages remained within the target of ≤16%. However, a low participation of members in relation to deposits is observed, fluctuating between 66% and 67%. These results could have been influenced by the decisions that cooperatives made during the pandemic. It is concluded that the COACs of segment four experienced a negative impact on economic-financial activities during the years 2020-2021; however, the projections reflect that the COACs will have the capacity to protect their savings and the contributions of the partners in the forecast years, but the patrimonial capacity will decrease.